Caveolin 1 Regulates the Tight Junctions between Sertoli Cells and Promotes the Integrity of Blood–Testis Barrier in Yak via the FAK/ERK Signaling Pathway - Qiu Yan; Tianan Li; Yong Zhang; Xingxu Zhao; Qi Wang; Ligang Yuan (Animals, 2024)
Yaks, a valuable livestock species endemic to China’s Tibetan plateau, have a low reproductive rate. Cryptorchidism is believed to be one of the leading causes of infertility in male yaks. In this study, we compared the morphology of the normal testis of the yak with that of the cryptorchidism, and found dysplasia of the seminiferous tubules, impaired tightness of the Sertoli cells, and a disruption of the integrity of the blood–testis barrier (BTB) in the cryptorchidism. Previous studies have shown that CAV1 significantly contributes to the regulation of cell tight junctions and spermatogenesis. Therefore, we hypothesize that CAV1 may play a regulatory role in tight junctions and BTB in Yaks Sertoli cells, thereby influencing the development of cryptorchidism. Additional analysis using immunofluorescence, qRT-PCR, and Western blotting confirmed that CAV1 expression is up-regulated in yak cryptorchidism. CAV1 over-expression plasmids and small RNA interference sequences were then transfected in vitro into yak Sertoli cells. It was furthermore found that CAV1 has a positive regulatory effect on tight junctions and BTB integrity, and that this regulatory effect is achieved through the FAK/ERK signaling pathway. Taken together, our findings, the first application of CAV1 to yak cryptorchidism, provide new insights into the molecular mechanisms of cell tight junctions and BTB. This paper suggests that CAV1 could be used as a potential therapeutic target for yak cryptorchidism and may provide insight for future investigations into the occurrence of cryptorchidism, the maintenance of a normal physiological environment for spermatogenesis and male reproductive physiology in the yak.